2017
DOI: 10.18632/oncotarget.22519
|View full text |Cite
|
Sign up to set email alerts
|

1,8-cineole prevents UVB-induced skin carcinogenesis by targeting the aryl hydrocarbon receptor

Abstract: 1,8-cineole is a natural monoterpene cyclic ether present in Eucalyptus, and has been reported to exhibit anti-inflammatory and antioxidant effects. However, the preventive effect of 1,8-cineole on skin carcinogenesis and the molecular mechanism of action responsible remains unknown. In the present study, we investigated the effect of 1,8-cineole on UVB-induced skin carcinogenesis. 1,8-cineole inhibited UVB-induced cyclooxygenase-2 (COX-2) protein and mRNA expression and prostaglandin E2 (PGE2) generation in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…This step is essential for the activation of tyrosine kinase receptors, such as EGFR, via phosphorylation of the C-terminal tail. We have confirmed that UV irradiation upregulates EGFR phosphorylation at Tyr1068, Tyr1045, and Tyr845 in HaCaT cells [10,44].…”
Section: Role Of Epidermal Growth Factor Receptor (Egfr) and Its Down...supporting
confidence: 69%
See 2 more Smart Citations
“…This step is essential for the activation of tyrosine kinase receptors, such as EGFR, via phosphorylation of the C-terminal tail. We have confirmed that UV irradiation upregulates EGFR phosphorylation at Tyr1068, Tyr1045, and Tyr845 in HaCaT cells [10,44].…”
Section: Role Of Epidermal Growth Factor Receptor (Egfr) and Its Down...supporting
confidence: 69%
“…Interestingly, UV irradiation brings about the dissociation of AhR and Src complexes, enabling Src to phosphorylate EGFR at Tyr845. Consequently, this phosphorylation increases cyp1a1 mRNA and COX-2 protein expression in HaCaT cells [ 44 ]. In short, UV-induced EGFR activation accelerates multiple signaling pathways involved in skin carcinogenesis.…”
Section: Role Of Epidermal Growth Factor Receptor (Egfr) and Its Downstream Signaling Pathways In Uv-induced Skin Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…They further showed the modulatory effects of the monoterpenoid on inammatory mediators in cultured human lymphocytes 7 and the rationale for its use as a mucolytic agent in treatment of upper and lower airway diseases. 8 Other preclinical screening of eucalyptol against microbial and viral infections, 9,10 gastric ulcer and colitis, 11,12 hepatic injury and oxidative stress, 13,14 pain and pneumonia, 15,16 cancer and tumours, 17,18 cardiovascular and neurodegenerative diseases 19,20 have also been attributed to its inherent ability to modulate redox and inammation processes.…”
Section: Introductionmentioning
confidence: 99%
“…The main essential oils from H. ellipticum studied using GC-FID and GC-MS by [116] . Cineole or eucalyptol is found to supress expression of COX-2 through UVB-induced carcinogenesis in HaCaT cells and also inhibit generation of prostaglandin E2 in the cells [117] . Pinene also, is found to reduce the growth of tumour in mice [118] .…”
Section: Roscoea Purpureamentioning
confidence: 99%